Surgical management and outcomes of non-missile open head injury: Report of 44 cases from a single trauma centre. (23rd February 2016) - Chen, Lei; Bao, Yinghui; Liang, Yumin; Wang, Yong; Jiang, Jiyao
Abstract: Objective : To retrospectively analyse the surgical management and outcomes of non-missile open head injuries (NMOHI). Methods : Forty-four patients who suffered from NMOHI were included. The Glasgow outcome score (GOS), computed tomography (CT), aetiology and outcomes and complications at discharge and during a 6-month follow-up were analysed. All patients underwent debridement. Intracranial haematoma evacuation, decompressive craniectomy (DC) or replacement were performed. Results : Motor vehicle accident and struck by/against were the most common causes (43.2% each). At admission, 33 patients had Glasgow coma scores (GCS) > 8 and 27 of them had a GCS score of > 13. Mean follow-up was 8.7 ± 4.3 months. All patients underwent debridement, 20 underwent bone fracture replacement and 27 underwent haematoma evacuation; 11 patients underwent haematoma evacuation and DC and one had bilateral DC. Twenty-seven patients showed good recovery; 11 patients had moderate disability; three patients had severe disability; and three patients died. After 6 months, 32 patients had good recovery and the morbidity of severe disability had decreased to 13.6%. Thirteen patients developed intracranial infection. Post-traumatic epilepsy and hydrocephalus was detected in three patients. Cerebrospinal fluid fistula was found in five patients. Only one patient developed a brain abscess after 6 months. Conclusions : NMOHI yielded satisfactory recovery and achieved good outcomes.